Developing E-Modul Based on Flipbook on Advance English in Nursing Anesthesiology (AENA) - Rusanti, Putu; Susandi, Ni Kadek Ary; Wulandari, Sarah Kartika (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
The benefit of e-learning is helping the students in learning process. Besides the material is accessible anywhere, the students also become more interested in learning because it is provided with links for games, audio and video. E-modul based on flipbook provides a flip effect which is like real reading and is equipped with sound, video, image and other features. The purpose of this research was (1) to identify the need analysis e-modul in Advance English in Nursing Anesthesiology (AENA) (2) to design and develop e-modul based on digital flipbook in Advance English in Nursing Anesthesiology (AENA). This research employed RnD (Research and Development) with ADDIE model. The material development process was carried out by analysis, design, development, and implementation. Data were collected by using questionnaire and were analyzed descriptively. The result of media expert validation was 88% and material expert validation was 91.6% which meant e-modul was good based on Gregory Formula. The result of implementation showed 81% students stated that they strongly agreed to use e-module in AENA because the material was clear and understandable. In addition, 74.3% of students stated they strongly agreed that the fontsize, colors, and images in the material were appropriate and understandable. It is expected that the results of the research can be used in classroom and for the further research can examine the effectiveness of using modul based on flipbook in the classroom.